2014
DOI: 10.1111/jsr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Is sleep‐related verbal memory consolidation impaired in sleepwalkers?

Abstract: SUMMARYIn order to evaluate verbal memory consolidation during sleep in subjects experiencing sleepwalking or sleep terror, 19 patients experiencing sleepwalking/sleep terror and 19 controls performed two verbal memory tasks (16-word list from the Free and Cued Selective Reminding Test, and a 220-and 263-word modified story recall test) in the evening, followed by nocturnal video polysomnography (n = 29) and morning recall (night-time consolidation after 14 h, n = 38). The following morning, they were given a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Using a similar experimental design, the same researchers investigated overnight declarative memory consolidation in 19 patients (M age ¼ 30 y) with sleepwalking (n ¼ 16) or sleep terror (n ¼ 3) compared to 19 controls (M age ¼ 32 y) [79]. Although the group of patients showed a more fragmented SWS than controls, both groups exhibited an overnight consolidation effect, improving their performance in both the verbal tests used from the evening to the morning session.…”
Section: Memory Consolidation In Parasomniasmentioning
confidence: 99%
“…Using a similar experimental design, the same researchers investigated overnight declarative memory consolidation in 19 patients (M age ¼ 30 y) with sleepwalking (n ¼ 16) or sleep terror (n ¼ 3) compared to 19 controls (M age ¼ 32 y) [79]. Although the group of patients showed a more fragmented SWS than controls, both groups exhibited an overnight consolidation effect, improving their performance in both the verbal tests used from the evening to the morning session.…”
Section: Memory Consolidation In Parasomniasmentioning
confidence: 99%
“…This finding further supports the idea that sleepwalking includes measurable daytime consequences and suggests that these manifestations are observable more readily after sleep deprivation. Daytime cognitive functioning in sleepwalkers was studied recently under normal daytime conditions and yielded negative results (Uguccioni et al ., ). However, the authors examined only verbal learning and sleep‐related episodic memory consolidation, and studies have yet to investigate sleepwalkers' daytime cognitive functioning following sleep deprivation.…”
Section: Introductionmentioning
confidence: 97%
“…Surprisingly, they reported the case of a sleepwalker who re-enacted the motor sequence of the learned task during an episode. On the contrary, in the study of Uguccioni et al [39], 7 patients showed episode of sleeptalking during the recording nights but the content of the sentences was not related to the list of words of the task.…”
Section: Neurocognitive Functions In Doamentioning
confidence: 76%
“…As SWS activity is known to be strongly associated to memory consolidation [38], a possible negative effect of these disorders on memory function is arguable. Uguccioni et al [39] tested verbal memory consolidation during sleep in patients affected by SW and ST. Two verbal memory tasks were employed in order to assess memory consolidation across the night. Furthermore, a learning task was used during the day to test consolidation after 9 h of wakefulness.…”
Section: Neurocognitive Functions In Doamentioning
confidence: 99%